Improving Learning Outcomes Of Multiplication Materials Mathematics Learning Methods (Drill) In Class IV SD Negeri 72 Kendari - linar linar (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aims to improve learning outcomes of mathematics in multiplication material using the drill method in class IV SD Negeri 72 Kendari. The drill method can improve students' mathematics learning outcomes in multiplication material in class IV SD Negeri 72 Kendari. This can be seen from the cycle I and cycle II test results. In the first cycle, the percentage of completeness is 70%, with an average value of 80. The mastery of student learning outcomes has increased in the second cycle, 90%, with an average value of 92.5. Thus the implementation of the class action has been successfully implemented because the predetermined performance indicators have been achieved.